Reusability study of zirconia catalyst toward photocatalytic degradation of remazol brilliant blue dye - Muhammad Farhan, Hanafi; Norzahir, Sapawe (Elsevier Ltd., 2020)
The regeneration and reusability study of EGZrO2 catalyst toward remazol brilliant blue (RBB) dye was carried out at specific optimum conditions. The overall degradation rate trends after seventh cycles shows that the photocatalytic process is stable from the first run at 99.8 and final seventh cycle at 83, with only just small decreases rate about less than 17. It is suggested that heat treatment during calcination at every cycle induced the catalyst aggregation and may also attribute during scouring of catalyst surface. No metal ions dissolution is detected by atomic absorption spectroscopy (AAS) analysis showing that the catalyst is more stable and also excellence photoresponse in visible light regions.